Highly fluorescent carbon dots as novel theranostic agents for biomedical applications. Issue 41 (15th October 2021) - Wan, Jiafeng; Zhang, Xiaoyuan; Fu, Kun; Zhang, Xin; Shang, Li; Su, Zhiqiang
Abstract : In this paper, we summarize the progress of drug-derived CDs in recent years, and introduce the classification of carbon dots, their synthesis methods and basic properties. Abstract : As an emerging fluorescent nanomaterial, carbon dots (CDs) exhibit many attractive physicochemical features, including excellent photoluminescence properties, good biocompatibility, low toxicity and the ability to maintain the unique properties of the raw material. Therefore, CDs have been intensively pursued for a wide range of applications, such as bioimaging, drug delivery, biosensors and antibacterial agents. In this review, we systematically summarize the synthesis methods of these CDs, their photoluminescence mechanisms, and the approaches for enhancing their fluorescence properties. Particularly, we summarize the recent research on the synthesis of CDs from drug molecules as raw materials and introduce the representative application aspects of these fascinating CDs. Finally, we look into the future direction of CDs in the biomedical field and discuss the challenges encountered in the current development.